Politisasi Identitas dalam Pemilu: Tinjauan Politik Hukum dan Prinsip Maqāṣid Al-Sharīʿah terhadap Ketahanan Nasional - Latifa, Dwi Ria (Tasyri' : Journal of Islamic Law, 2025)
Indonesia as a multicultural democratic country faces vulnerability to identity political mobilization, especially those rooted in primordial issues such as religion and ethnicity. This phenomenon was prominent in the 2017 Jakarta Regional Election and the 2019 Presidential Election, which showed the increasing social polarization due to digital disinformation and SARA-based campaigns. This situation is a threat to national resilience, as well as showing the insynchronity between the constitutional principle of non-discrimination and the weak campaign regulations in Law No. 7 of 2017. This study uses a mixed approach between normative and empirical. The normative approach is used to analyze the political, legal and regulatory aspects of election campaigns, while the empirical approach is carried out through field studies using data triangulation techniques from official documents, NGO reports, and digital campaign archives. The results of the study show three main findings: (1) The ambiguity of the definition of "identity politics" in election regulations leads to law enforcement that tends to be subjective; (2) The use of digital technology such as deepfakes and political bots contributed to a 300% surge in SARA content during the 2019–2024 period; (3) There is a tension between the principle of freedom of expression and the prohibition of primordial campaigns, which have not been adequately accommodated within a positive legal framework. The discussion linked the findings to the principles of maqāṣid al-sharīʿah, particularly in the aspects of ḥifẓ al-dīn (protection of religion), ḥifẓ al-nafs (protection of the soul), and ḥifẓ al-'aql (protection of reason), as a normative basis to stem the politicization of identity that threatens national resilience. The study recommends progressive revisions to the Election Law, the integration of artificial intelligence (AI) technology in the KPU surveillance system, and the mainstreaming of Islamic values that uphold justice and unity in digital campaigns.